53.3k views
3 votes
Given f(x) = 2x2 + 4x - 3 and g(x) = 5x - 2, find f(x) - g(x).

Must show all work to receive credit! Show your work in the box below

Given f(x) = 2x2 + 4x - 3 and g(x) = 5x - 2, find f(x) - g(x). Must show all work-example-1
User Brhardwick
by
5.2k points

2 Answers

2 votes

Answer:

f(x) - g(x) = 2x^2 - x - 1

Explanation:

f(x) = 2x^2 + 4x - 3 g(x) = 5x - 2

f(x) - g(x) = (2x^2 + 4x - 3) - (5x - 2)

= 2x^2 + 4x - 3 - 5x + 2

= 2x^2 - x - 1

User Anthony Jack
by
5.6k points
6 votes

Answer:

its the same steps as the other one I answered for you except subtract

Explanation:

x-1

User DarkVision
by
4.9k points